A dilatometry study of the influence of green density on anisothermal and isothermal shrinkage of plain iron green parts. (26th May 2020) - Baselli, S.; Molinari, A.
ABSTRACT: The influence of green density between 6.5 and 7.3 g cm −3 on the anisothermal and isothermal shrinkage of atomized plain iron was investigated by dilatometry. The geometrical activity deriving from the extension of the interparticle contact areas and the structural activity provided by the defectiveness of the interparticle contacts promote anisotropic anisothermal shrinkage starting from 500°C up to the bcc to fcc iron transformation. It displays a minimum at 6.9 g cm −3, resulting from the combined effects of the thermodynamic driving force and of geometrical and structural activity. Anisothermal shrinkage is caused by an anisotropic increase in the internal radius of the neck. Anisotropic isothermal shrinkage is smaller than the anisothermal one and is almost independent on green density. No anisothermal shrinkage was observed on the tapped powder, demonstrating that anisothermal shrinkage in green specimens is due to geometrical and to structural activity introduced by prior cold compaction.